2003
DOI: 10.1590/s1517-74912003000400012
|View full text |Cite
|
Sign up to set email alerts
|

Short-term immunosuppressive therapy does not affect the density of the pre-existing bone around titanium implants placed in rabbits

Abstract: The aim of this study was to evaluate the influence of the administration and withdrawal of cyclosporin A/nifedipine on the bone density in a lateral area adjacent to implants placed in rabbits. Two screw-type titanium implants were placed bilaterally in twenty-eight New Zealand rabbits. The animals were assigned to one of the following groups and received daily subcutaneous injections for 14 days: Groups A and C: vehicle (dimethyl sulfoxide); Groups B and D: CsA (10 mg/kg) plus nifedipine (50 mg/kg). The anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…CsA therapy may affect bone healing due to its mechanism of action. T‐lymphocytes are the main target of CsA administration, and previous study (Duarte et al, ) in rats showed that T cells perturbations are associated with the development of primary osteoporosis. In this context, the immune system dynamically contributes in bone mineral metabolism and T‐lymphocytes play a pivotal role in the development of CsA‐induced osteopenia (Duarte et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…CsA therapy may affect bone healing due to its mechanism of action. T‐lymphocytes are the main target of CsA administration, and previous study (Duarte et al, ) in rats showed that T cells perturbations are associated with the development of primary osteoporosis. In this context, the immune system dynamically contributes in bone mineral metabolism and T‐lymphocytes play a pivotal role in the development of CsA‐induced osteopenia (Duarte et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…T‐lymphocytes are the main target of CsA administration, and previous study (Duarte et al, ) in rats showed that T cells perturbations are associated with the development of primary osteoporosis. In this context, the immune system dynamically contributes in bone mineral metabolism and T‐lymphocytes play a pivotal role in the development of CsA‐induced osteopenia (Duarte et al, ). T cell suppression leads to a high metabolism state, in which bone turnover is increased resulting in elevated bone resorption rate compared to the bone formation, and subsequently a lower percentage of trabecular bone volume and development are achieved (Duarte et al, ; Movsowitz et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations